Identification of student's misconceptions in chemical bonding topic using four-tier diagnostic test. (March 2020) - Mahmudah, A; Nahadi,; Firman, H
Abstract: The purpose of this study was to identify misconceptions by measuring the level of students understanding in chemical bonding topic using four-tier multiple choice diagnostic test. The research method was descriptive and involved 77 students of senior high school in South Tangerang. The results shows that the overall the students misconception on chemical bonding topic was in low category (15.14%). The level of confidence in this study was highly significant because it can provide information about student's conceptual understanding. Students encountered the most misconceptions when determining bonds in microscopic scale. As an evidence, misconceptions in the concept of determining microscopic ionic and covalent bonds results to medium category (41.56%), and metal bonds with medium category (37.66%). This student's misconception was due to the limited conceptual knowledge and low visual-spatial abilities.